Cheaper and more durable proton exchange membrane - -, -
The demand for fossil fuel increased year by year but the sources of fossil fuel is decreasing. Nowadays, researchers are looking at alternative energy sources to reduce the dependency on fossil fuel. Hydrogen is an interesting energy source alternative to be studied. The aim of this study is to perform environmental and economic assessment for two hydrogen production pathways namely from methane (Case 1) and ethanol (Case 2). Rigorous simulation of both processes was done using Aspen Plus version 8.6. The reaction of steam reforming from methane and ethanol were kinetic based simulation. The kinetic data was obtained from the literature. The reactions were modelled using RPlug blocks with rearranged Langmuir-Hinselwood-Hougen-Watson (LHHW) kinetic model and power law kinetic model. The purification of hydrogen was based on rigorous model in the simulation. The validation results show good agreement with results found in the literature. In addition, sensitivity analysis was carried out observing the effect of several parameters such as temperature, pressure, catalyst weight and feed ratio to the reactor performance for both cases. After that, environment and economic assessment were performed. The data obtained were used for comparison purposes. The environment assessment was based on life cycle assessment (LCA) to evaluate the environmental impact of all processes involved in hydrogen production using GaBi software based on ReCiPe method. The LCA functional unit used for both case studies was 1 kg of hydrogen. Overall, 16 categories impact assessment were carried out and only three were highly significant namely climate change, fossil depletion and water depletion. Case 2 shows high impact on climate change with 30.84 kg CO2 eq compared to Case 1 with 9.44 kg CO2 eq. On the other hand, Case 2 shows higher fossil fuel resource depletion with 12.54 kg oil eq compared to Case 1 with 4.044 kg oil eq. Furthermore, Case 2 also has a higher water resources depletion of 23.35 m3 eq. compared to Case 1 which is only 4.01 m3 eq. The capital cost for Case 1 is 7.92% less compared to Case 2. Meanwhile, the total utilities cost for Case 1 is 12.81% less compared to Case 2. In conclusion, the hydrogen production from methane, Case 1, is environmental friendlier and less costing in term of CAPEX and OPEX than Case 2.